2012
DOI: 10.1088/0960-1317/22/6/065026
|View full text |Cite
|
Sign up to set email alerts
|

Improving the performance of biomimetic hair-flow sensors by electrostatic spring softening

Abstract: We report improvements in the detection limit and responsivity of biomimetic hair-flow sensors by electrostatic spring softening. Applying a dc-bias voltage to our capacitive flow sensors results in a reduced sensory threshold, improving the mechanical transfer and flow detection limit by more than 6 dB. We further show that the sensor's responsivity for airflows is also improved on application of high-frequency ac-bias voltages to the sensor's capacitive structures with little sensitivity to the bias frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 31 publications
5
32
1
Order By: Relevance
“…Improvement of these electronics, by reduction of its noise, will help to bring the detection threshold for the accelerometer towards the thermal noise-limited threshold. Similar differences between measured and (calculated) thermal noise levels have been observed for our previously reported biomimetic hair flow sensors [21,22].…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Improvement of these electronics, by reduction of its noise, will help to bring the detection threshold for the accelerometer towards the thermal noise-limited threshold. Similar differences between measured and (calculated) thermal noise levels have been observed for our previously reported biomimetic hair flow sensors [21,22].…”
supporting
confidence: 87%
“…We showed that this MEMS hair-based accelerometer has a resonance frequency of 320 Hz, a detection threshold of 0.10 m s 22 and a dynamic range of more than 35 dB. Further, the accelerometer has low responsivity to airflow, clear directivity and a bias instability of 5 Â 10 23 m s…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, the resonance frequency is observed to decrease (about 20%). Overall, measurements are in good agreement with modeling and it is shown clearly that DC-biasing leads to a larger sensitivity below the sensor's resonance frequency ( Figure 6) [1]. …”
Section: Dc-biasingsupporting
confidence: 74%
“…Despite the fact that we show the benefits of such schemes for our flow-sensors only, the two-port models used are far more generic and suggest suitability of these schemes in a much broader range of applications. With this in mind we have put the results of these three schemes in this one overview but do not claim new results relatively to earlier reported studies, notably references [1][2][3].…”
Section: Introductionmentioning
confidence: 90%